HIGH-TECH PRODUCTION AND INNOVATIVE ACTIVITY IN UKRAINE IN THE CONTEXT OF THE ECONOMIC POTENTIAL OF THE COUNTRY - Voitko, Serhii; Vyshnevska, Anastasiia (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2020)
The article discusses the concepts of "potential" and "economic potential", analyzes their interpretation by different scientists, and gives reasons  for the importance of its awareness by countries for which it determines their specialization. The economic potential of high-tech production in Ukraine is analyzed by such indicators as the part of enterprises that inculcate innovations (products and/or technological processes), the part of the amount of the realized innovative products (commodities, services) in the general volume of the realized products (commodities, services) of industrial enterprises, the costs of innovative activity, export of high-tech products, the amount of workers per a million habitants of country, that are engaged in developments and researches, and middle and high-tech industry (including building) in the percent of value-added of production of Ukraine. The article consideres the place of Ukraine in the Global Innovation Index. Comparative description of Ukraine, Poland, and Vietnam is fulfilled according to the indexes of exports of high-tech products (in billion USD) and amount of workers per a million habitants of the country that is engaged in developments and scientific researches. The paper analyzes how the share of high-tech products affects the development of the economy and competitiveness of the country. It shows the costs of scientific and technical research and development of Ukraine as compared with the United States, Germany and Japan. It also considers the importance of investment activity in Ukraine for the development of the country's economic potential. The article indicates the problems that hinder the development of technological and scientific potentials of Ukraine. Recommendations are given on the possibilities of increasing the economic potential of high-tech national production in order to increase Ukraine's competitiveness in the world market.